Entrepreneurship as a Key Competence - Implications for the Education Process in Poland - Nowacka, Urszula (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The ever escalating pace of civilizational changes in the social and economic fields, as well as in science and technology triggers a change of employers’ expectations with respect to employees’ competences. Thus, a need has arisen for enterprising and creative employees with the ability of critical and at the same time, creative thinking, with high interpersonal competence, who can obtain and effectively process information and based on that make decisions, and who are real team players, understanding the need for lifelong learning. Such competences have a significant impact on an independent, responsible and auspicious life. The changes led the European Parliament and the Council to adopt a key competence framework to which entrepreneurship and initiative have been, among other competences, classified.The aim of the article is to define conditions related to creation of entrepreneurship as a key competence in the process of education in Poland, both among students of upper-secondary schools and tertiary education students. The article uses the findings of research conducted in Poland regarding evaluation of acquired key competences and identification of competences and qualifications sought by employers.